Hemostatic changes associated with menopausal hormone therapy. Comparison of transdermal and oral administration - Połać, Ireneusz; Borowiecka, Marta; Stetkiewicz, Tomasz; Nowak, Paweł (Menopause Review/Przegląd Menopauzalny, 2012)
Hormone therapy (HT) is a popularly recommended treatment for eliminating or alleviating the symptoms of menopause. It is established that combined preparations containing estrogen and progestin are related with a small, but clinically significantly increased risk of arterial and venous thrombosis, may increase myocardial infarction and stroke in women. The aim of our study was to confront the hemostatic effects of taking oral and transdermal HT in postmenopausal Polish women compared with non-users (controls) matched for age for 6 months. The concentration of thrombin-activatable fibrinolysis inhibitor (TAFI) was measured using ELISA kit Imclone Tafi’s produced by American Diagnostica GmbH. Generated thrombin was measured according to the method described by Lau el al. Plasmin formation in plasma was determined by chromogenic substrate (Chromozym PL). The activity of generated thrombin was statistically higher in plasma of women after o-HT (72.6 ±8.5 mOD/min) than in patients with t-HT (53.7 ±10.1 mOD/min) and controls (51.2 ±10 mOD/min). Amidolytic plasmin activity was the highest in controls (84.5 ±10.2 mOD/min). The value of plasmin activity in women after o-HT treatment was lower (61.9 ±7.9 mOD/min) compared to patients taking t-HT (77.7 ±14.5 mOD/min). The highest level of TAFI was observed in patients after oral hormones (80.38 ±8.23%); women on transdermal HT had 61.58 ±9.81% and the lowest concentration of TAFI was noted in the control group (44.70 ±10.16). The influence of HT on hemostasis has been largely attributed to the estradiol part of the preparation, although progestogen can also affect observed changes. The effect we observed may in part be explained by the dose and type of progestogen.